Volunteering and Community Connection: Benefits of Community Volunteering to Connect People Together Through School Children and Build Harmonious Community - Shanti Nandana Wijesinghe (International Journal of Children, 2026)
Unlike traditional forms of volunteering, modern volunteering has new purposes and outcomes. It is now recognized as a legitimate way for individuals to formally participate in local affairs through community level action. In many countries, volunteers have a nationally legislated institutional structure and set of principles, and rights and responsibilities, which is collectively agreed upon to be adhered to and safeguarded by all volunteers and the organizations and programs they are involved in. These arrangements have modern made volunteer action somewhat professional. The stories of thousands of volunteers, all around the world, demonstrate that modern volunteering generates benefits to both individual as well as community as a whole. It connects individuals to their communities and helps promoting the attitude of connection, belonging and shared identity and rebuilding “community” which is claimed to be at risk of fragmentation. This assertion was examined with a community level social development project in Northern Sri Lanka planned and conducted entirely by a group of young community volunteers, and the conclusion that community volunteering can be successfully applied as a strategy to connect people together and promote attitudes of harmony within socially and culturally diverse community contexts is presented here in this paper.
Keywords: Community connection; school children in Sri Lanka; sustainable peace; volunteerism; youth empowerment